On generalizations of quantum Simpson's and quantum Newton's inequalities with some parameters - Chanon Promsakon; Muhammad Aamir Ali; Hüseyin Budak; Mujahid Abbas; Faheem Muhammad; Thanin Sitthiwirattham (AIMS Mathematics, 2021)
In this paper, we prove two identities concerning quantum derivatives, quantum integrals, and some parameters. Using the newly proved identities, we prove new Simpson's and Newton's type inequalities for quantum differentiable convex functions with two and three parameters, respectively. We also look at the special cases of our key findings and find some new and old Simpson's type inequalities, Newton's type inequalities, midpoint type inequalities, and trapezoidal type inequalities.